Oxidized graphene oxide hybrid silicon dioxide-silver binuclear molecularly imprinted polymer as well as preparation method and application thereof

Through the preparation of hybrid silica-silver binuclear molecular imprinted polymers of graphene oxide, the problem of isolation and enrichment of six flavonoids in small flower mice was solved, efficient extraction and detection was achieved, and Shiga Fukushima was used to solve the problem of separation and enrichment of six flavonoid compounds in small flower mice. Bacteria have antibacterial effects.

CN119264344AInactive Publication Date: 2025-01-07ZHANJIANG EXPERIMENTAL STATION CHINESE ACAD OF TROPICAL AGRI SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411379818.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art has failed to effectively realize the isolation and enrichment of six flavonoid compounds (soglycopene, apigenin, kaempferol, luteolin, quercetin and genistein) in small flower mice, resulting in difficulty in extraction and detection.

Method used

The hybrid silica-silver binuclear molecular imprinting polymer (SiO2-Ag@GO) was prepared by surface molecular imprinting technology and precipitation polymerization method. As a solid phase extraction column material, Sozoin was used as template molecules and AM It is a functional monomer and EGDMA as a crosslinking agent to achieve specific adsorption and enrichment of flavonoid compounds.

Benefits of technology

The isolation and enrichment of 6 flavonoids in the small flower mouse worm was successfully achieved, which improved the extraction efficiency and selectivity, simplified the detection process, and showed the antibacterial effect on Shigella Fukura.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264344A_ABST
    Figure CN119264344A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of molecular imprinting, in particular to a graphene oxide hybridized silicon dioxide-silver binuclear molecularly imprinted polymer as well as a preparation method and application thereof. The preparation method comprises the following steps: with acacetin as a template molecule, SiO2-Ag-coated GO as a core, AM as a functional monomer and EGDMA as a cross-linking agent, preparing the molecularly imprinted polymer by using a surface molecular imprinting technology and a precipitation polymerization method. The robinin'specificity-like 'molecularly imprinted polymer synthesized by the invention has the optimal specific adsorption capacity. According to the present invention, the AMIPs-SPE-HPLC-MS / MS method is adopted to detect the six flavonoid compounds in the acanthus ilicifolius, the recovery rate is good, the detection limit under the standard mass concentration is low, the active flavonoid substances in the marine acanthus ilicifolius can be extracted, separated and determined, the further verification results show that the AMIPs has the strong antibacterial effect after selectively adsorbing the flavonoid active substances, and the AMIPs can be used for preparing the active flavonoid compounds in the marine acanthus ilicifolius. Good application potential is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of molecular imprinting, and in particular to an oxidized graphene oxide hybridized silicon dioxide-silver dual-core molecular imprinting polymer and a preparation method and application thereof. Background Art

[0002] Flavonoids are special compounds with 2-phenylchromone structure that exist in nature in the form of glycosides or in a free state. The hydroxy derivatives of flavonoids have complex structures and diverse types. The marine mangrove Acanthaceae ebracteatus contains a wide variety of herbal resources and a variety of secondary metabolites, such as robinin, apigenin, quercetin, etc. Among them, robinin is a natural flavonoid compound that can be extracted and separated from Acanthaceae ebracteatus, Carthamustininctorius, Anthurium versicolor, Dryoathyrium boryanum (wild) and Lamiaceae plants, and is mostly used in medical research and the cosmetics industry. Flavonoids have a variety of biological activities, such as antioxidant, anti-inflammatory, antibacterial, anti-osteoporosis, anti-tumor, immunomodulatory, and protective of the heart and nervous system, and have a great effect on human health. Since flavonoids cannot be directly synthesized in animals, high-throughput separation of small-molecule natural flavonoids with strong activity and easy extraction has attracted much attention. The study of flavonoid extraction, purification and detection methods has very important research value for the analysis of new natural medicinal flavonoid small-molecule compounds.

[0003] Molecular imprinted solid phase extraction (MISPE) is a very important sample pretreatment method with the advantages of simple operation, high preconcentration coefficient, and low solvent consumption. It is also a research hotspot in the fields of natural product separation, lead compound screening, and solid phase extraction. Flavonoids vary greatly in molecular size, hydrophilicity, hydrophobicity, charge and other properties, and their content in natural medicinal plants is low. In addition, the sample matrix is ​​complex, making extraction and separation difficult. Molecular imprinted polymers (MIPs) as extraction column materials can enrich the active ingredients in natural medicinal plants. They have good extraction performance and high sample recovery rate, which can improve the directional separation effect of active ingredients and shorten the detection time. MIPs are used to simulate the specific binding mechanism of "enzyme and substrate" in the process of biorecognition. The template molecule combines with the functional monomer to form a complex. After the reaction, the template is washed away, leaving a specific recognition site, which can specifically recognize the target molecule. MIPs have high selectivity, reusability and chemical stability, making them the preferred material with low cost and high efficiency.

[0004] With the discovery of new flavonoids, the methods of their extraction, separation and detection are constantly being explored and innovated. However, in the prior art, there is no report that MIPs can simultaneously separate and enrich the six flavonoids (robinin, apigenin, kaempferol, luteolin, quercetin and genistein) in Acanthus parviflorus. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide an oxidized graphene oxide hybrid silica-silver dual-core molecularly imprinted polymer and a preparation method and application thereof.

[0006] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is:

[0007] In a first aspect, a method for preparing an oxidized graphene oxide hybrid silica-silver binuclear molecularly imprinted polymer is provided, which comprises the following steps: using acaciatin as a template molecule, SiO2-Ag@GO as a core, AM as a functional monomer, and EGDMA as a cross-linking agent, and utilizing surface molecular imprinting technology and precipitation polymerization to prepare the molecularly imprinted polymer.

[0008] Furthermore, the preparation method of SiO2-Ag@GO specifically includes the following steps:

[0009] First, 1.0 mg EDC and 0.5 mg NHS were added to 10 mL of ethanol solution containing 3 mg / mL graphene oxide and reacted for 30 min to activate the carboxyl groups on the surface and edge of graphene oxide to obtain oxidized graphene oxide GO; 1.0 g SiO2@Ag-NH2 was dispersed in 10 mL of ultrapure water and then added to 10 mL of activated GO and reacted at 328 K for 10 h to completely coat the layered GO on the SiO2@Ag-NH2 microspheres; the mixture was centrifuged at 9000 rpm / min for 10 min, the precipitate was collected, and the uncoated GO was washed with ultrapure water to obtain SiO2@Ag@GO.

[0010] Furthermore, the preparation method of SiO2@Ag-NH2 specifically includes the following steps:

[0011] 0.01 g SiO2@Ag was dispersed in a solution consisting of 10 mL toluene and 1 mL APTES and stirred in nitrogen at 303 K for 5 h; centrifuged at 6000 rpm / min for 10 min, and the precipitate was collected; the precipitate was washed three times with dimethyl sulfoxide and ethanol; finally, vacuum dried at 333 K for 3 h to obtain SiO2@Ag-NH2 microspheres.

[0012] Furthermore, the preparation method of SiO2@Ag specifically includes the following steps:

[0013] Take 1.0g SiO2 and bake it at 120℃, add it to 600mL anhydrous ethanol and mix it thoroughly; after SiO2 is evenly distributed in the anhydrous ethanol, add equal amounts of water and NaOH to the reaction system and stir continuously; after reaching adsorption equilibrium, add 30mL of silver nitrate, 15.2g / L, at a rate of 1mL / min, react with NaOH, and reduce with ethanol; after a certain reaction time, the product SiO2@Ag is obtained by multiple centrifugation-redispersion-washing, and dried at room temperature for standby use.

[0014] In a second aspect, a molecular imprinted polymer prepared by the above method is provided.

[0015] In a third aspect, a solid phase extraction column is provided, wherein the molecular imprinting polymer according to claim 5 is provided in the solid phase extraction column.

[0016] In a fourth aspect, a use of a molecular imprinting polymer or a solid phase extraction column comprising a molecular imprinting polymer in detecting flavonoid compounds in Acanthus parviflorus is provided.

[0017] A fifth aspect provides use of a molecularly imprinted polymer or a solid phase extraction column comprising a molecularly imprinted polymer for separating and enriching flavonoid compounds in Acanthus parviflorus.

[0018] Furthermore, Acanthus parviflorus includes 6 flavonoid compounds, namely robinin, apigenin, kaempferol, luteolin, quercetin and genistein.

[0019] The beneficial effects of the present invention are:

[0020] The present invention uses SiO2-Ag@GO as a dual core, and uses surface molecular imprinting technology and precipitation polymerization to prepare acacia molecular imprinting polymers (AMIPs). TEM, SEM, FTIR, XRD and HPLC-MS / MS are used to characterize the structure and properties of AMIPs. Multiple adsorption kinetic models are used to analyze the selective adsorption differences of AMIPs on small molecular flavonoids, and the separation and enrichment methods of 6 flavonoids in Acanthus parviflorus are explored for the first time. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 . Flow chart of molecular imprinting polymer synthesis and MISPE preparation procedures;

[0022] Figure 2 .Chemical structures of six flavonoid compounds;

[0023] Figure 3a .UV spectra of robinin and different functional monomers;

[0024] Figure 3b.UV spectra of acaciatin and AM at different ratios;

[0025] Figure 4 .XRD spectra of Ag2O, SiO2, SiO2-Ag@GO and AMIPs;

[0026] Figure 5a .FT-IR spectra of SiO2, oxidized graphene oxide, Ag2O and SiO2@Ag;

[0027] Figure 5b . FT-IR spectra of robinin and AMIPs / NIPs;

[0028] Figure 6 . TEM and SEM images of SiO2-Ag (a) and SiO2-Ag@GO (b) and SEM images of AMIPs (c) and ANIPs (d);

[0029] Figure 7 Adsorption kinetics analysis of robinin on AMIPs and ANIPs (a), adsorption isotherm analysis (b), Langmuir and Freundlich analysis (c) and Scatchard plot analysis (d);

[0030] Figure 8 .Selective analysis of six flavonoid AMIPs (a) and AMIPs;

[0031] Fig. 9 .6 compounds (n=3) selected different loading solvents (a), eluents (b), elution solvents (c) and elution times (d);

[0032] Fig.10a .Total ion chromatogram of 6 flavonoids extracted from Acanthus parviflorus by AMISPE;

[0033] Fig.10b .Total ion chromatogram of six flavonoids in Acanthus parviflorus determined by HPLC-MS / MS;

[0034] Fig.11 .Evaluation of the inhibitory effect of AMIPs on Shigella flexneri after selective adsorption of flavonoid active substances from Acanthus parviflorus. DETAILED DESCRIPTION

[0035] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.

[0036] Example

[0037] 1. Materials and Methods

[0038] 1.1 Reagents

[0039] Food grade SiO2 particle size ranges from 7-40nm and specific surface area ranges from 50-400m 2 / g. AgNO3 and ammonium hydroxide (NH3·H2O) were purchased from Sigma, methacrylic acid (MAA), acrylamide (AM), 1-ethyl-3-(-dimethylaminopropyl)-carbodiimide (EDC), 2-imido-N-hydroxysuccinimide (NHS), ethylene glycol dimethacrylate (EGDMA) and 2,2'-azobisisobutyronitrile (AIBN) were purchased from Alfa Aesar, UK. Tetraethyl orthosilicate (TEOS), 3-aminopropyltrimethoxysilane (APTES) and 3-(trihydroxysilyl)-propylmethyl phosphate (THPMP) were purchased from Merck. Toluene (analytical grade) and methanol were purchased from Sigma Aldrich (St. Louis, USA). Ultrapure water was obtained from the laboratory using Merck's milliq water purification system. All other chemicals met all experimental requirements.

[0040] Acanthus parviflorus was purchased from Guangdong Huangfu Pharmaceutical Co., Ltd. (Zhanjiang, China). Robinin, apigenin, kaempferol, luteolin, quercetin, and genistein (purity 98%) were purchased from Chengdu Ruifens Biotechnology Co., Ltd. The chemical structures are shown in Figure 1 shown.

[0041] 1.2 Preparation of SiO2-OH

[0042] After heating SiO2 at 373K for 12h, the mixture was cooled to room temperature and soaked in 3.0mol / L HCl solution for 1h. The sample was washed with ultrapure water until the pH was neutral to remove the acid. Finally, the sample was rinsed with an appropriate amount of methanol and dried at 333K for 24h to obtain SiO2-OH. It was sealed and stored for subsequent use.

[0043] 1.3 Preparation of SiO2@Ag

[0044] Take 1.0g SiO2-OH and bake it at 120℃, add it to 600mL anhydrous ethanol and mix it thoroughly. After SiO2 is evenly distributed in anhydrous ethanol, add equal amounts of water and equal amounts of NaOH to the reaction system and stir continuously. Since SiO2-OH has adsorption capacity, a NaOH / water-rich adsorption layer with a thickness of only a few nanometers can be gradually formed on the surface of SiO2-OH, which serves as a nanophase reactor. After reaching adsorption equilibrium (24h), silver nitrate (30mL, 15.2g / L) is added at a rate of 1mL / min, reacts with NaOH, and is reduced with ethanol. After a certain reaction time, the product SiO2@Ag is obtained by multiple centrifugation-redispersion-washing, and dried at room temperature for standby use.

[0045] 1.4 Preparation of SiO2@Ag@NH2

[0046] SiO2@Ag (0.01 g) was dispersed in a solution consisting of 10 mL toluene and 1 mL APTES, and stirred in nitrogen for 5 h at 303 K. The solution was centrifuged at 6000 rpm / min for 10 min, and the precipitate was collected; the precipitate was washed three times with dimethyl sulfoxide and ethanol; and finally dried under vacuum at 333 K for 3 h to obtain SiO2@Ag-NH2 microspheres.

[0047] 1.5 Preparation of SiO2@Ag@GO

[0048] First, 1.0 mg EDC and 0.5 mg NHS were added to 10 mL of ethanol solution containing 3 mg / mL graphene oxide, and the reaction was carried out for 30 min to activate the carboxyl groups on the surface and edge of graphene oxide to obtain oxidized graphene oxide (GO); 1.0 g SiO2@Ag-NH2 was dispersed in 10 mL of ultrapure water, and then added to 10 mL of activated GO, and reacted at 328 K for 10 h to completely coat the layered GO on the SiO2@Ag-NH2 microspheres. Centrifuge at 9000 rpm / min for 10 min, collect the precipitate, wash the uncoated GO with ultrapure water, and finally obtain SiO2@Ag@GO.

[0049] 1.6 UV spectroscopy analysis

[0050] According to the structure and polymerization principle of the template molecule, combined with the results of ultraviolet spectral analysis, the optimal ratio between the template molecule and the functional monomer was preliminarily predicted. MAA, 4-VP, and AM were used as functional monomers, acetonitrile solution was used as solvent, a certain concentration of acacia solution was prepared, and an equal amount of functional monomers were added. At room temperature, the template and the functional monomer were mixed in different molar ratios and stirred for 30 minutes. The change in the maximum absorption wavelength in the reaction system was measured by ultraviolet spectrophotometry to determine the optimal functional group. According to the above method, the acacia concentration was unchanged, and the ratio of template to functional monomer was 1:0, 1:2, 1:4, 1:6 and 1:8 respectively to determine the optimal reaction ratio.

[0051] 1.7 Synthesis of molecularly imprinted polymers (AMIPs / ANIPs)

[0052] With robinin as template, AM as functional monomer, EGDMA as crosslinker, AIBN as initiator, and acetonitrile as pore former, robinin, 50 mg SiO2@Ag@GO microspheres, and 350 μL AM were added to 30 mL methanol and prepolymerized at 4 °C for 30 min. Then, 0.045 mL crosslinker EGDMA and 20 mg AIBN were added to the reaction system, and the mixture was ultrasonically dispersed and dissolved.

[0053] The air in the reaction system was removed by nitrogen filling, and nitrogen was filled in the reaction system for 10 minutes. The reaction system was sealed and then placed in a water bath shaker at 60°C and 160 rpm / min to continue the reaction for 18 hours. ANIPs were prepared by the same method without adding template molecules. Finally, the mixture was centrifuged at 6000 rpm / min for 15 minutes, and the precipitate was washed 5 times with different solutions (acetonitrile, tetrahydrofuran, acetone), and AMIPs / ANIPs were obtained after drying.

[0054] 1.8 Drawing a standard curve

[0055] Prepare 1 mg / ml mixed standard stock solution. Then dilute to working solutions with concentrations of 5, 10, 50, 100, and 500 μg / L. Establish HPLC-MS / MS method and draw standard curve. Use C18 (Cosmosil C18-EB column, 4.6ID×150mm), column temperature of 25°C, 1% ammonium formate (5mmol / L) aqueous solution A and 100% acetonitrile B as mobile phases, 30% A and 70% B at 0-5min; 70% A and 30% B at 5.1-7.0min; 60% A and 20% B at 7.1-9.0min. The minimum flow rate is 200 μL / min, and the injection volume is 2 μL. Negative ion scanning mode, specific parameters of parent particle, daughter ion, collision voltage and degrouping voltage are shown in Table 1.

[0056] Table 1. Mass spectrometry parameters and parent ions, daughter ions, collision voltages and degrouping voltages of six flavonoid compounds

[0057]

[0058] 1.9 Adsorption and competitive selectivity

[0059] The adsorption performance of AMIPs / ANIPs on robinin, apigenin, kaempferol, luteolin, quercetin and genistein in a mixed standard solution (10 mg / L) was studied. After reaching adsorption equilibrium, the polymer was separated by centrifugation at 6000 rpm / min for 10 min. The active ingredients in the supernatant were determined by HPLC-MS / MS. The amount of robinin adsorbed by AMIPs / ANIPs was calculated according to the following formula (1):

[0060]

[0061] Among them, C0 and C e (μg / L) are the initial concentration and equilibrium concentration of acaciatin in the matrix solution, V(L) is the volume of the standard solution, and m(g) is the mass of AMIPs or ANIPs.

[0062] The Scatchard (Equation 2), Langmuir (Equation 3), and Freundlich (Equation 4) adsorption models were used to fit the data. The former is applicable to saturated homogeneous adsorbents such as molecularly imprinted polymers, while the latter assumes that adsorption occurs on heterogeneous surfaces and that there are interactions between the adsorbed molecules. The following formula was used:

[0063]

[0064] Where Q max is the maximum saturated adsorption capacity (mg / g), and Ks is the dissociation constant.

[0065]

[0066] Among them C e is the concentration of the solution after adsorption, A and K are constants.

[0067]

[0068] Where C e is the solution concentration after adsorption, K is a constant, and n is the adsorption index.

[0069] Using the imprinting efficiency (I e ) was used to evaluate the selectivity of the polymer, and the imprinting efficiency was calculated using the following formula (Equation 5):

[0070]

[0071] Where Q MIP and Q NIP represent the adsorption capacity, respectively.

[0072] The distribution coefficient (KD), selectivity coefficient (κ) and relative selectivity coefficient (κ') of AMIPs and ANIPs were calculated according to the following formulas (Formula 6, 7, 8):

[0073]

[0074]

[0075]

[0076] The same method was used to determine the adsorption selectivity of ANIPs. C0 is the initial concentration, C e is the adsorption equilibrium concentration, K D is the distribution coefficient relative to other structural analogs, and the selectivity coefficient is the ratio of the distribution coefficients of robinin to each other analyte in the polymer. The selective sites of six compounds were compared in this experiment. The relative selectivity coefficient is the ratio of the selectivity of AMIPs and ANIPs in a single analyte in a mixed standard solution. A competitive recognition study between AMIPs and robinin was also conducted. 10 mg of AMIPs was added to a 1 mL, 10 mg / mL flavonoid mixture containing robinin, apigenin, kaempferol, luteolin, quercetin and genistein. After reaching adsorption equilibrium, the mixture was shaken at room temperature for 60 min, then centrifuged at 6000 rpm / min for 10 min, and the polymer was collected. Each experiment was repeated 3 times.

[0077] 1.10 Preparation of AMIPs solid phase extraction column

[0078] A frit was placed at one end of a 5 mL polyethylene solid phase extraction column, with the rough side of the frit facing the polymer. 10 mg of AMIPs was taken and activated with 5 mL of acetone and added to the column. Finally, another frit was placed on top of the AMIPs. Before extraction and purification, the extract was thoroughly washed and activated with water, acetic acid-methanol (20:80, v / v), and acetonitrile.

[0079] 1.11 Optimization of solid phase extraction conditions

[0080] The main purpose of this part of the experiment was to optimize the loading, leaching and elution solvents of the solid phase extraction column. After each step of the experiment, the leaching solution was collected and dried in nitrogen at 25°C. The residue was redissolved in 1 mL of acetonitrile, and the resulting solution was filtered through a nylon membrane with a pore size of 22 μm and analyzed by HPLC-MS / MS. Each experiment was repeated 3 times. The loading solvents considered were methanol, acetonitrile and water. A standard solution containing 6 flavonoid molecules (1 mL, 10 mg / L) was loaded onto the AMISPE solid phase extraction column containing AMIPs. Washing solvents (2 mL) of n-hexane, carbon tetrachloride (CCl4), CH2Cl2, ACN, MeOH and water were used. The elution solvent was acetic acid-methanol in different ratios (3:7, 2:8, 1:10, v / v).

[0081] 1.12 Testing of solid phase extraction in actual samples

[0082] This part of the experiment is mainly the application of AMISPE column combined with HPLC-MS / MS in actual samples. The real samples were verified at concentrations of 0, 5, 25, 50, and 100 μg / L. The analytical time was optimized (2, 4, 8, 16, 32, 64 min, n = 3) to obtain the analytical curve. The samples of Acanthus parviflorus were dried under natural conditions for 2 weeks, 1.0 g of sample was weighed, 50 mL of methanol-water (1:1, v / v) was added to each sample, ultrasonicated for 20 min, and then centrifuged at 5000 rpm for 5 min. The ultrasonication and centrifugation were repeated 3 times, and the supernatant was collected. AMIPs were extracted by HPLC-MS / MS. The extract was evaporated to dryness by nitrogen blowing. The extract was dissolved in 1 mL of acetonitrile and added to the prepared AMISPE. The extract was collected under the above-optimized optimal extraction conditions; and the loading solution was obtained by filtration through a 0.22 μm nylon membrane, and the content was determined by HPLC-MS / MS.

[0083] 1.13 Evaluation of the inhibitory effect of AMIPs on Shigella flexneri

[0084] Use an inoculation loop or inoculation needle to reach into the bacterial tube and pick up the colony for transplantation. Reach into the slant culture tube, first drag an inoculation line from the bottom to the top of the slant, then draw a winding line from bottom to top, or directly draw a winding line from bottom to top. After the inoculation is completed, sterilize the mouth of the culture tube with flame, plug it with cotton, and place it at 37°C for incubation. After incubation, a single colony can be obtained on the surface of the plate. Use an inoculation loop and operate on the clean bench to select a colony with clear edges and relatively large colonies. Just make a loop and touch it. Remember not to insert it. Then quickly transfer it to a 15ml test tube of nutrient broth without agar. The whole process should not exceed 5 seconds. Then seal it well and put it in a shaker for incubation overnight. Take the cultured bacteria and use the plate streaking method mentioned above for incubation. Use a 1000ul gun tip to insert the culture medium (insert it to the bottom and rotate it to ensure that the culture medium in the hole can be taken out). To remove the culture medium in the hole, you need to use the tip of the gun tip to pick it up. Be sure to keep it close to the waste tank to prevent it from scattering on the clean bench. Use a pipette to repeatedly aspirate to ensure that the solution is evenly mixed. After the injected AMIPs suspension is cultured for 24 hours, observe the results.

[0085] 2 Results and discussion

[0086] 2.1 Preparation of AMIPs

[0087] The spatial structure between the template molecule and the imprinted polymer determines the specificity of its binding site recognition. The key stage affecting molecular imprinting recognition is the combination of the template and the monomer to form a stable host-guest complex during the preassembly process. Since the cross-linker and initiator have relatively little effect on the interaction between the template and the functional monomer, EGDMA and AIBN are not present in the spectral study.

[0088] In this study, UV spectroscopy was used to screen the types and proportions of functional monomers, such as Figure 3a As shown. After the template molecule interacted with MAA, 4-VP and AM, the maximum absorption wavelength around 330nm changed to varying degrees. Among them, the maximum absorption peak shift of the UV spectrum of acaciatin and AM prepolymer was the most significant, while the maximum absorption wavelength after the interaction of acaciatin with 4-VP or MAA did not change significantly. This may be because the template molecule is acidic, and not only has π-π conjugation and hydrogen bond interactions with AM, but can also form stable ionic bonds. Therefore, AM was selected as the functional monomer in this experiment. Similarly, according to the different ratios of template molecules to functional monomers, UV spectral analysis shows (such as Figure 3b As shown in Figure 2, when the ratio of template molecule to functional monomer is 1:4, the wavelength red shift of the polymer is the most significant. As the amount of AM increases, the maximum absorption wavelength of the mixture hardly changes, indicating that more AM will not enhance the interaction between the two. Therefore, the optimal ratio of template molecule to AM is determined to be 1:4.

[0089] Precipitation polymerization is the most widely used molecular imprinting polymerization technology. The morphology and particle size of the spherical imprinted polymers prepared by this method are related to factors such as the type and amount of the solvent used, the solubility of the template molecule, the type and amount of the functional monomer and cross-linker, and the polymerization temperature. Compared with bulk polymerization, the imprinted polymers prepared by precipitation polymerization do not require grinding and screening processes, and the operation is simpler. The recognition characteristics of molecular imprinted polymers are not only related to the interaction between functional monomers, but also to the formation of spatial sites, which is related to other polymerization conditions, such as cross-linkers. EGDMA is an acrylic ester compound with two unsaturated C=C double bonds in its structure, and is often used as a cross-linker in polymerization reactions. Therefore, this study screened and optimized the type and amount of cross-linkers, and synthesized a series of polymers. The results showed that the optimal molar ratio was acacia:AM:EGDMA=1:4:25.

[0090] 3.2 Characterization of AMIPs

[0091] XRD characterization of the intermediate products during the synthesis process Figure 4 As shown. The results show that Ag2O has two characteristic peaks at two Theta30-40 and one characteristic peak at 50-60 and 60-70. SiO2 did not show good crystal structure characteristics, but there were characteristic peaks between TwoTheta 20-30. Due to chemical synthesis and GO encapsulation, the characteristic peaks of SiO2@Ag@GO were weakened and covered. Under the action of crosslinkers and initiators, AMIPs covered the characteristic protruding peaks of SiO2, leaving only the two characteristic peaks of Ag. These results show that AMIPs were successfully synthesized.

[0092] The FT-IR spectrum confirmed the successful preparation (Figure 5). -1 The vibration at is the characteristic peak of Ag2O, about 1200cm -1 The vibration at 949cm is the characteristic peak of SiO2, while -1 Other bands observed nearby are the bending vibrations of Si-OH

[33] . When Ag2O encapsulates SiO2, a certain polarization occurs at 1444 cm -1 and 1276cm -1 Vibration occurs at Figure 5a ). This indicates that SiO2@Ag was successfully synthesized. In addition, 1730cm -1 and 1630cm -1 The peaks near 1465.52cm are characteristic peaks of GO. After synthesizing AMIPs / ANIPs, polarizations of different sizes were generated. -1 The peak at 2870.83 cm is the benzene ring of robinin. -1 The peak at 1311.21cm is the vibration of the CH bond on the benzene ring.-1 The peak at 2972.18cm indicates the presence of an ether bond. -1 The vibration at can be inferred that acaciatin successfully binds to AMIPs ( Figure 5b ). All the peaks indicate that AMIPs were successfully prepared.

[0093] The morphology of AMIPs / ANIPs was characterized by SEM and TEM ( Figure 6 The prepared SiO2@Ag nanoparticles have a relatively uniform particle size between 50 and 100 nm, indicating that a dual-core structure has been formed ( Figure 6 a). After GO coating, the particle size of the nanoparticles is between 150-200, the surface is convex, and there is obvious agglomeration ( Figure 6 b). The double core with higher electron density represents SiO2@Ag nanoparticles, and the outer layer with lower electron density represents the adhesion of MIPs on SiO2@Ag@GO. The core-shell structure is clear. Transmission electron microscopy shows that its thickness is about 5-10nm. After further preparation, the surface of AMIPs is rough, and each particle surface has evenly distributed lamellar wrinkles, the microspheres are irregular in shape, the surface area of ​​AMIPs is large, and AMIPs grow on the layered structure of graphene oxide ( Figure 6 c), indicating that the template may affect the growth of spherical particles during the synthesis process. In contrast, ANIPs rarely exhibit this structure, and the surface wrinkles on the surface of ANIPs are less ( Figure 6 d).

[0094] 3.3 Kinetics and isothermal adsorption of AMIPs / ANIPs

[0095] The adsorption performance of AMIPs / ANIPs was studied by static adsorption experiments. As the initial concentration of robiniain increased, the amount of robiniain adsorbed on AMIPs increased ( Figure 7 a). Compared with ANIPs, the equilibrium adsorption test showed that the adsorption amount of robinin was higher, the adsorption process tended to equilibrium at 9 h, and the adsorption amount of robinin reached a peak at 10 h, while the amount of ANIPs decreased after 10 h.

[0096] The adsorption isotherm of AMIPs / ANIPs was obtained ( Figure 7 b). In AMIPs, the adsorption amount increases with the increase of robinin concentration. When the concentration reaches the maximum value of 25 mg / mL, the binding capacity of robinin is close to saturation and then begins to decline. Compared with ANIPs, AMIPs can bind to robinin specifically. The Langmuir and Freundlich equation models have better fitting effects, among which the Langmuir model is more suitable ( Figure 7c), indicating that when AMIPs are strongly adsorbed through intermolecular interactions, the adsorption capacity is saturated and uniform. According to Scatchard analysis, AMIPs have two adsorption sites ( Figure 7 d). The maximum adsorption of acaciatin by AMIPs was 32.0346 mg / g and 105.9960 mg / g at the high and low points, respectively. This result indicates that sieve holes are formed on the surface of AMIPs, which may bind to SiO2@Ag@GO to form dual sites. However, for imprinted polymers with different binding sites, when the substrate concentration is low, the contribution of the low affinity site is often ignored when determining the binding constant of the high affinity site, so the Scatchard analysis method has certain limitations in determining the corresponding binding parameters; similarly, when the substrate concentration is high, the binding of the low affinity site still contributes to the binding of the high affinity site.

[0097] 3.4 Selection of AMIPs / ANIPs

[0098] The KD-AMIPs of the six flavonoid AMIPs were 1.7266~0.3278mL / g, while the KD-AMIPs of ANIPs were 0.5495~02908mL / g( Figure 8 a), indicating that AMIPs have better adsorption and molecular recognition capabilities. Figure 8 As shown in (b), in the adsorption process of 6 flavonoids by AMIPs, robinin showed the highest selectivity, and the order of adsorption capacity was robinin> apigenin> quercetin> kaempferol> luteolin> genistein. The k' value represents the affinity of the recognition site to the template molecule, and the affinities for apigenin, kaempferol, luteolin, quercetin, and genistein are 2.0969, 3.6720, 4.7407, 2.9383, and 5.2665, respectively; all are greater than 2.0, indicating that its adsorption selectivity is higher than that of ANIPs. In addition, compared with other flavonoids, AMIPs showed stronger adsorption capacity for robinin, including structural analogs such as apigenin, kaempferol, luteolin, and quercetin. This result highlights the significance of imprinted cavity specificity in recognizing structural analogs of template molecules. Compared with AMIP, non-imprinted polymer ANIPs showed lower adsorption capacity for several different molecules, which was attributed to the free distribution of active functional groups within the AMIP network space.

[0099] 3.5 MISPE Condition Optimization

[0100] In order to determine the best purification and enrichment capacity of AMIPs, the loading, washing and elution solvents were optimized in this experiment. The selective recognition of robinin and its structural analogs was fully considered during separation. The binding reaction is easy to occur in organic solvents, and acetonitrile increases the adsorption capacity of robinin ( Fig. 9a). By comparing the adsorption amount and equilibrium value, acetonitrile was selected as the best loading solvent. The actual sample also showed good affinity for acaciatin. The washing step can enhance the interaction between the template and the polymer and remove other impurity molecules by washing. The washing and elution solvents for AMIPs are 1:8 CH2Cl2 and acetic acid-methanol ( Fig. 9 b,c), optimized the elution time of 6 compounds ( Fig. 9 d), the results show that the desorption process can be completed within 16 min, which is the optimal desorption time. Robinin showed a strong affinity for the two polymers, which may be due to their similar skeleton structure, binding site and shape.

[0101] 3.6 Method Validation

[0102] The linear range, relative standard deviation, correlation coefficient and detection limit of the method were evaluated with reference to Sante / 11945 / 2015 and other literature. Under the optimized extraction conditions, the mixed standard solution of acetonitrile with different concentrations was verified to detect 7 concentration levels of mixed standard substances in the range of 5-500 μg / L. The linear regression coefficient was 0.9921-0.9982. The detection limits (LODs) and quantification limits (LOQs) were calculated by multiplying the signal-to-noise ratio by 3 times and 10 times, respectively. The detection limits of the standard items were 2.31-4.05 μg / L, and the detection limits were 6.50-12.20 μg / L (Table 2).

[0103] Table 2. Linear range, regression coefficient, detection limit and quantification limit of 6 components (n = 5)

[0104]

[0105] 3.7 Actual sample analysis

[0106] The separation and purification performance of AMIPs for six active ingredients was evaluated in actual samples. The actual contents of robinin, apigenin, kaempferol, luteolin, quercetin and genistein in Acanthus parviflorus were 1.45, 3.22, 7.84, 2.34, 2.56 and 3.10 μg / g, respectively. The accuracy and precision of the method were evaluated by adding three concentrations (0, 5, 25, 50 and 100 μg / L) of the six active substances. The results showed that robinin and other components were in good agreement with previous studies. Partial liquid chromatography-mass spectra of robinin, apigenin, kaempferol, luteolin, quercetin and genistein extracted by AMIPs were coupled with HPLC-MS / MS ( Fig.10b ). When added to the sample, the signal of Acanthus parviflorus increased. The successful application of AMIPs confirmed that flavonoids in Acanthus parviflorus can be separated and detected.

[0107] 3.8 Evaluation of the inhibitory effect on Shigella flexneri

[0108] The antibacterial effect of AMIPs prepared in the present invention on Shigella flexneri was determined by plate method. Fig.11 As shown in the figure, the MIC50 of AMIPs against the bacteria is 0.05 μg / mL. Comparison of the antibacterial effects of AMIPs and vancomycin revealed that the antibacterial activity of 0.05 μg / mL AMIPs against Shigella flexneri is similar to that of vancomycin.

[0109] The SiO2 surface has a large number of functionalized hydroxyl groups, which can be combined with silane functionalization reagents and introduce functional groups with specific properties into the SiO2 interface to carry out target chemical reactions or continue to load functional nanoparticles. The pore volume and size are adjustable. Increasing the pore volume can increase the loading amount of guest substances, and further adjust the pore size of MIPs to anchor functional guest substances of specific particle sizes, thereby increasing the corresponding particle size performance effect, thereby obtaining excellent chemical, mechanical, thermal and hydrothermal stability. Oxidized graphene oxide (GO) is a commonly used carrier material with rich functional groups. It can be used as a GO carrier to enhance the adsorption capacity of MIPs. The GO surface in the carrier is rich in oxygen groups, which can be modified into hydroxyl or carboxyl groups to increase the formation of coordination bonds, enhance the electrostatic force and van der Waals force during the MIP adsorption process, and improve the MISPE performance.

[0110] The present invention uses acaciatin as a template molecule, SiO2-Ag@GO as a core, AM as a functional monomer, and EGDMA as a cross-linking agent, and the synthesized AMIPs have the best specific adsorption capacity. The adsorption performance evaluation shows that the adsorption capacity and selectivity of the template molecule are greater than those of ANIPs, indicating that the template molecule and the functional monomer undergo copolymerization to produce a synergistic effect. The Langmuir model fits the isothermal adsorption data well. The AMIPs-SPE-HPLC-MS / MS method was used to detect 6 flavonoid compounds in Acanthus parviflorus, with a good recovery rate and a low detection limit at the standard mass concentration. The method is simple and accurate, and significantly improves the detection efficiency and precision. It can be used for trace detection of flavonoids and can be used to inhibit bacterial growth, and has good application prospects in the qualitative and quantitative analysis of flavonoids in marine mangroves.

[0111] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0112] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing an oxidized graphene oxide hybrid silica-silver binuclear molecularly imprinted polymer, characterized in that: The following steps are involved: Molecularly imprinted polymers were prepared by surface molecular imprinting technology and precipitation polymerization, with acaciatin as the template molecule, SiO2-Ag@GO as the core, AM as the functional monomer and EGDMA as the cross-linker.

2. The preparation method according to claim 1, characterized in that: The preparation method of SiO2-Ag@GO specifically includes the following steps: First, 1.0 mg EDC and 0.5 mg NHS were added to 10 mL of ethanol solution containing 3 mg / mL graphene oxide and reacted for 30 min to activate the carboxyl groups on the surface and edge of graphene oxide to obtain oxidized graphene oxide (GO); 1.0 g SiO2@Ag-NH2 was dispersed in 10 mL of ultrapure water and then added to 10 mL of activated GO and reacted at 328 K for 10 h to completely coat the layered GO on the SiO2@Ag-NH2 microspheres; the mixture was centrifuged at 9000 rpm / min for 10 min, the precipitate was collected, and the uncoated GO was washed with ultrapure water to obtain SiO2@Ag@GO.

3. The preparation method according to claim 2, characterized in that: The preparation method of SiO2@Ag-NH2 specifically includes the following steps: 0.01 g SiO2@Ag was dispersed in a solution consisting of 10 mL toluene and 1 mL APTES and stirred in nitrogen at 303 K for 5 h; centrifuged at 6000 rpm / min for 10 min, and the precipitate was collected; the precipitate was washed three times with dimethyl sulfoxide and ethanol; finally, vacuum dried at 333 K for 3 h to obtain SiO2@Ag-NH2 microspheres.

4. The preparation method according to claim 3, characterized in that: The preparation method of SiO2@Ag specifically comprises the following steps: Take 1.0g SiO2 and bake it at 120℃, add it to 600mL anhydrous ethanol and mix it thoroughly; after SiO2 is evenly distributed in the anhydrous ethanol, add equal amounts of water and NaOH to the reaction system and stir continuously; after reaching adsorption equilibrium, add 30mL of silver nitrate, 15.2g / L, at a rate of 1mL / min, react with NaOH, and reduce with ethanol; after a certain reaction time, the product SiO2@Ag is obtained by multiple centrifugation-redispersion-washing, and dried at room temperature for standby use.

5. The molecularly imprinted polymer prepared by the method according to any one of claims 1 to 4.

6. A solid phase extraction column, characterized in that: The molecular imprinting polymer according to claim 5 is arranged in the solid phase extraction column.

7. Use of the molecular imprinting polymer according to claim 5 or the solid phase extraction column according to claim 6 in detecting flavonoids in Acanthus parviflorus.

8. Use of the molecular imprinting polymer according to claim 5 or the solid phase extraction column according to claim 6 in separating and enriching flavonoids from Acanthus parviflorus.

9. The use according to claim 7 or 8, characterized in that: Acanthus parviflorus contains 6 flavonoid compounds, namely, robinin, apigenin, kaempferol, luteolin, quercetin and genistein.

Citation Information

Patent Citations

  • High-performance and highly-controllable core-shell-type imprinted sensor, preparation method and application thereof

    CN106947018A

  • Preparation method and extraction method of larch flavonoid active ingredient magnetic molecularly imprinted polymer

    CN111333777A

  • AU2020100965A4